2021
DOI: 10.1101/2021.12.21.21268058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of CoronaVac, ChAdOx1, BNT162b2 and Ad26.COV2.S among individuals with prior SARS-CoV-2 infection in Brazil

Abstract: Background. COVID-19 vaccines have proven highly effective among SARS-CoV-2 naive individuals, but their effectiveness in preventing symptomatic infection and severe outcomes among individuals with prior infection is less clear. Methods. Utilizing national COVID-19 notification, hospitalization, and vaccination datasets from Brazil, we performed a case-control study using a test-negative design to assess the effectiveness of four vaccines (CoronaVac, ChAdOx1, Ad26.COV2.S and BNT162b2) among individuals with l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Twenty seven (6.7%) were protocols, seven (1.7%) were vaccine safety studies, and 370 (91.6%) only examined immunogenicity and reactogenicity in people who were vaccinated. Of the remaining 76 studies, we were able to extract data from 53,2223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374 which gave us a sample size of 100 190 476 participants from 15 countries. Supplementary table 2 presents a summary of the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty seven (6.7%) were protocols, seven (1.7%) were vaccine safety studies, and 370 (91.6%) only examined immunogenicity and reactogenicity in people who were vaccinated. Of the remaining 76 studies, we were able to extract data from 53,2223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374 which gave us a sample size of 100 190 476 participants from 15 countries. Supplementary table 2 presents a summary of the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies included high risk populations (defined as having more than one chronic condition),27404143474869 of which two studies included patients who were immunocompromised in a subset of the high risk populations 4869. Of the 53 included studies, 19 investigated the protectiveness of vaccines against covid-19 variants of concern or variants of interest, including alpha (B.1.1.7), beta (B.1.351), gamma (P.1), delta (B.1.617.2), and omicron (B.1.1.529) 22263032343738394142444748495761636870…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were lower after only a single dose: 70-90% for death, 55-95% for severe infection, 35-93% for symptomatic disease, and 30-80% for any infection. Some studies found lower effectiveness in special populations, including residents of long-term care facilities 84,149,150 , priority groups 122 , the elderly 147 , and those previously infected 113,179 . Heterogeneities between studies made direct comparisons of efficacy/effectiveness for variants difficult.…”
Section: Results Of Covid-19 Vaccine Studiesmentioning
confidence: 99%
“…Previous studies, conducted prior to the Omicron epidemic wave, found that primary vaccination (two doses) afforded protection against reinfection beyond that provided by a prior infection(69) and that a booster dose significantly increase such protection. (10) In contrast, Shrestha et al found that primary vaccination did not provide additional protection (Hazard Ratio, 0.77; 95% CI, 0.53-1.12) against SARS-CoV-2 re-infection among previously infected people during the first month of the Omicron wave. (11) Furthermore, evidence is lacking for the additional benefit of booster vaccination against Omicron infection in individuals with a prior infection, which is needed to inform vaccination policies for this sub-population.…”
Section: Introductionmentioning
confidence: 98%